Extended producer responsibility (EPR) and packaging regulations in Argentina: reflections on the aspects associated with the blocking of the draft legislation initiatives - Schamber, Pablo Javier (2022)
For more than two decades there has been an on-going debate in Argentina about the draft bills presented to congress for the management of packaging waste and the notion of extended producer responsibility. This article analyses the points of agreement and controversies among the stakeholders with respect to their approach to the debate. The analysis basically covers the discussions around three key issues related to a proposed packaging waste management system: the obliged subjects liable to make contributions, the state or private nature of the entity responsible for managing such system, and the role of the waste pickers and their organizations. A number of secondary sources were consulted (legislative files, dossiers, public records and bibliography), and several interviews were conducted to a number key actors (specialists in this field, legislative advisers, waste picker’s referents, law makers, public servants and technical experts) for the writing of this paper.